2015
DOI: 10.3109/10903127.2015.1037480
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Nitroglycerin Safety in Inferior ST Elevation Myocardial Infarction

Abstract: Patients with inferior ST elevation myocardial infarction (STEMI), associated with right ventricular infarction, are thought to be at higher risk of developing hypotension when administered nitroglycerin (NTG). However, current basic life support (BLS) protocols do not differentiate location of STEMI prior to NTG administration. We sought to determine if NTG administration is more likely to be associated with hypotension (systolic blood pressure < 90 mmHg) in inferior STEMI compared to non-inferior STEMI. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It would be reasonable to expect a higher rate of adverse events as the penumbra increases; this comparison may make RVMI appear unsafe, whereas the increased risk may be instead due to increased area of infarction (regardless of RVMI being the additional region involved). This theory is supported by the results of Robichaud et al , where isolated inferior infarction was the safest at 6.10% and the rate of adverse events in concomitant inferior and RVMI was actually lower than the rate in concomitant inferior and other myocardial infarctions at 8.14% compared with 8.40%, respectively 12…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It would be reasonable to expect a higher rate of adverse events as the penumbra increases; this comparison may make RVMI appear unsafe, whereas the increased risk may be instead due to increased area of infarction (regardless of RVMI being the additional region involved). This theory is supported by the results of Robichaud et al , where isolated inferior infarction was the safest at 6.10% and the rate of adverse events in concomitant inferior and RVMI was actually lower than the rate in concomitant inferior and other myocardial infarctions at 8.14% compared with 8.40%, respectively 12…”
Section: Discussionmentioning
confidence: 57%
“…Two factors mean the synthesised result for nitroglycerin 400 μg sublingual may be overstating the actual risk. First, McConnell et al compared joint inferior and RVMI with isolated inferior infarction 12 13. It would be reasonable to expect a higher rate of adverse events as the penumbra increases; this comparison may make RVMI appear unsafe, whereas the increased risk may be instead due to increased area of infarction (regardless of RVMI being the additional region involved).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall hypotension rate was 8.2%, suggesting that hypotension will occur in one in every 12 patients who are administered glyceryl trinitrate, and that this will be regardless of the region where the infarction is occurring. The paper concluded "although it is widely recommended in the medical literature to use caution when administering nitroglycerin to patients with inferior STEMI, the only study supporting this statement is a retrospective cohort study published in 1989 by Ferguson et al" (5).…”
Section: -Present: New Cohort Evidence Is Presentedmentioning
confidence: 99%
“…Because nitroglycerin may precipitate hypotension in patients with acute lower-wall and associated VRIG STEMI, its prehospital administration routine may not be safe. 15 Oxygen therapy has been commonly used in the initial treatment of patients with STsegment elevation myocardial infarction, based on the belief that supplemental oxygen may increase the oxygen supply to the ischemic myocardium and, therefore, reduce myocardial injury, which is supported by laboratory studies and an early clinical study. Other studies, however, have suggested a potential adverse physiological effect of supplemental oxygen, with reduced coronary blood flow, increased coronary vascular resistance, and the production of reactive oxygen species that contribute to vasoconstriction and reperfusion injury.…”
Section: Stmentioning
confidence: 99%